2015
DOI: 10.1007/s00423-015-1356-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated low flow pump system for the treatment of refractory ascites: a single-center experience

Abstract: The Alfapump system is a useful system in the treatment of patients suffering from therapy refractory ascites. However, due to the high level of comorbidities, careful patient selection and postoperative monitoring are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…We screened 309 references; 40 were selected for full‐text retrieval. Of these, nine were included in the analysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened 309 references; 40 were selected for full‐text retrieval. Of these, nine were included in the analysis …”
Section: Resultsmentioning
confidence: 99%
“…The methodological analysis of each study identified discrepancies in three studies in which median or mean MELD score was >15 (Table ). As MELD score might influence the rate of adverse events related to the procedure, sensitivity analyses excluding the Thomas, the Solbach and the Wong studies were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in keeping with those observed in this study, in which bacterial infections, hepatic encephalopathy, and AKI were also the most common cirrhosis‐related adverse events with 40, 17, and 13 episodes, respectively, in 40 patients. In a recent study that reports a single‐center experience with 10 patients who were treated with the alfa pump system, prerenal AKI was also reported as a common complication …”
Section: Discussionmentioning
confidence: 99%
“…Diuretics (e.g., furosemide and potassium-conserving diuretics) and a water-clearance mediator (e.g., tolvaptan) are available [71] . Hemodynamic disorders such as hepatic venous obstruction and portal thrombosis may develop if no response is observed after diuretic induction [72] . The most frequent cause of morbidity and mortality after LT is not immunological rejection but infectionrelated complications [73][74][75] .…”
mentioning
confidence: 99%